Kırgız destanları. (Ankara Ankara Ankara Ankara Ankara Ankara)
<15> cilt (2. c. 311 sayfa ; 3. c. 302 ; 4. c. 82 sayfa ; 5. c. 341, [2] sayfa ; 6. c. 528 sayfa ; 8. c. 129 sayfa ; 9. c. 228 sayfa ; 10. c. 128 sayfa ; 11. c. 147 sayfa ; 12. c. 140 sayfa ; 13. c. 151 sayfa ; 14. c. 290 sayfa ; 15. c. 299 sayfa ; 16. c. 514 sayfa ; 17. c. 298 sayfa)